KINERJA PEGAWAI DI UNIT PELAKSANA TEKNIS PENILAIAN PENDIDIKAN DI DINAS PENDIDIKAN DAN KEBUDAYAAN PROVINSI SULAWESI TENGAH - Lakala, Muhamad Suhud (Katalogis, 2017)
This research was conducted at the Employee Performance in the Technical Executing Unit of Education Assesment At Central Sulawesi Board Of Education And Culture. The research method was qualitative descriptive which data type used primary and secondary. Data were collected from observation, interviews, documentation, and triangulation. To get informants used purposive technique. Data analysis techniques used qualitative models. The theory of Robbins was used in this research that consist of 3 (three) aspects namely motivation, ability and opportunity. From this research, it was known that the performance of Employee Performance in the Technical Executing Unit of Education Assesment At Central Sulawesi Board Of Education And Culture still lack of effectiveness. The aspect of motivation of employee was still lack related to discipline, such as employee attendance during the work hours. In addition, another factor that caused employee ran into the rules of organization which there was not specifically penalty given to employee who did not obey. Besides, both aspects of the ability and the opportunity were basically good. The ability of employee knowledge and work mastery has been perfect based on the needs of the organization.Â